2018
DOI: 10.1111/jpn.12977
|View full text |Cite
|
Sign up to set email alerts
|

Benzoic acid in nursery diets increases the performance from weaning to finishing by reducing diarrhoea and improving the intestinal morphology of piglets inoculated with Escherichia coli K88+

Abstract: A total of 224 weaned pigs (DanBred sows x PIC 337 sires) with an average body weight (BW) of 6.37 ± 0.34 kg (21 days of age) were used to evaluate how different levels of benzoic acid fed to weaning pigs orally inoculated with Escherichia coli (K88 ) affected the nursing and grow-finishing performance, the physicochemical properties of the intestine, the volatile fatty acid concentration in the caecum and the incidence of diarrhoea. Pigs were randomly allocated in an experimental design of randomized blocks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Moreover, evidence suggested that benzoic acid increases digestive enzyme activity and improves jejunal and ileum morphology leading to greater nutrient digestibility in both poultry and swine [37,38]. This increase in nutrient uptake not only reduces nonpathogenic diarrhea, but also improves the growth performance of nursery pigs [39]. In order to determine the impact of benzoic acid alone or in combination with butyrate on nutrient digestibility, a negative control (basal diet) group was added at the University of Arkansas.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence suggested that benzoic acid increases digestive enzyme activity and improves jejunal and ileum morphology leading to greater nutrient digestibility in both poultry and swine [37,38]. This increase in nutrient uptake not only reduces nonpathogenic diarrhea, but also improves the growth performance of nursery pigs [39]. In order to determine the impact of benzoic acid alone or in combination with butyrate on nutrient digestibility, a negative control (basal diet) group was added at the University of Arkansas.…”
Section: Discussionmentioning
confidence: 99%
“…Thymol, carvacrol, and eugenol were also tested (individually or as essential oils) in many previous studies which reported the positive effects of these bioactives against several E. coli strains both in vivo and in vitro [15,[31][32][33]. Moreover, several in vivo studies demonstrated the usefulness of OA in controlling PWD in orally challenged piglets [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…The dose of inoculum used in this trial was based on a previous trial by our group [28], however, it was low if compared to other trials [35][36][37]. Nevertheless, the challenge seemed to be effective at increasing the diarrhea among the piglets as higher values were observed for the first period evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…On the first experimental day, the piglets received an intramuscular dose (0.15 mL) of tulathromycin antibiotic (Draxxin ® , Zoetis, Parsippany-Troy Hills, NJ, USA), for the control of respiratory diseases. According to Silveira [28], this antibiotic acts mainly in the lungs, which could minimize any other factor that is not associated with enteric challenges.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation